Factors that influence the stress level of first semester students at high school of health sciences Husada Hospital Jakarta - Ernawati, Ernawati; Keisha Ayu Aida Muryanto; Adea Yusti; Yurita Mailintina (Jurnal EduHealth, 2024)
Background: Academic pressure, which comes from students' efforts to achieve high grades and avoid failure, is the main trigger for stress among students. Stress levels tend to be high in students who have difficulty adapting to academic demands, while those who can adapt generally experience lower stress levels. Stress experienced by students can have both good and bad impacts, especially related to increased academic workload which can affect academic performance and GPA. Research objective: to understand academic pressure, stress levels, and the factors that cause first semester students to withdraw. Research method: used was quantitative with a cross-sectional design, involving 131 respondents. Research results: show that there is a strong relationship between conflict, pressure and change and the factors that cause stress in first semester students at one of the private universities in Jakarta. Student characteristics, including age, gender, and study program, were also identified in this study.